Beginning T-SQL 2008 - Kellenberger, Kathi (Apress, 2012)
Welcome to Beginning T-SQL 2008. This book introduces you to the language known as T-SQL, also called Transact-SQL. It’s the fundamental language that you need to know in order to work productively with Microsoft’s database management system known as SQL Server. Almost everything that you do in SQL Server boils down to T-SQL commands, whether you write them yourself or whether a tool generates them for you. If you want to be successful in a career involving SQL Server, then it helps to master the underlying language. To whet your appetite and to give you an idea of what you’re in for, here is a simple example of a T-SQL statement. It’s a simple query to list all the databases hosted on SQL Server: SELECT name FROM sys.databases;